Three-Dimensional Human Cardiac Tissue Engineered by Centrifugation of Stacked Cell Sheets and Cross-Sectional Observation of Its Synchronous Beatings by Optical Coherence Tomography. (22nd February 2017) - Haraguchi, Yuji; Hasegawa, Akiyuki; Matsuura, Katsuhisa; Kobayashi, Mari; Iwana, Shin-ichi; Kabetani, Yasuhiro; Shimizu, Tatsuya
Abstract : Three-dimensional (3D) tissues are engineered by stacking cell sheets, and these tissues have been applied in clinical regenerative therapies. The optimal fabrication technique of 3D human tissues and the real-time observation system for these tissues are important in tissue engineering, regenerative medicine, cardiac physiology, and the safety testing of candidate chemicals. In this study, for aiming the clinical application, 3D human cardiac tissues were rapidly fabricated by human induced pluripotent stem (iPS) cell-derived cardiac cell sheets with centrifugation, and the structures and beatings in the cardiac tissues were observed cross-sectionally and noninvasively by two optical coherence tomography (OCT) systems. The fabrication time was reduced to approximately one-quarter by centrifugation. The cross-sectional observation showed that multilayered cardiac cell sheets adhered tightly just after centrifugation. Additionally, the cross-sectional transmissions of beatings within multilayered human cardiac tissues were clearly detected by OCT. The observation showed the synchronous beatings of the thicker 3D human cardiac tissues, which were fabricated rapidly by cell sheet technology and centrifugation. The rapid tissue-fabrication technique and OCT technology will show a powerful potential in cardiac tissue engineering, regenerative medicine, and drug discovery research.